Supply chain risk mitigation strategies in the electrical energy sector in South Africa - Jonathan, Ellsworth Chouncey (Vaal University of Technology, 2018)
Interferences to supply chains, regardless of whether they are regular, unplanned or intentional, are progressively distorting supply chain execution. Given that such disruptions are probably not going to diminish, for the time being, supply chain risk mitigating solutions will assume an undeniably critical part of the management of supply chains. This research acknowledges the existence of an extensive variety of approaches to mitigate risks across supply chains, yet argues that most methodologies may not be reasonable if the culture of an organisation does not support them. Supply Chain Risk Management (SCRM) has rapidly become of significance to the world economy. Though the supply of electrical energy in Southern Africa affects the economies of nations around the globe, it has received too little consideration from the literary community. The focus of this thesis is to expand the field of SCRM by analysing how different risk assessment and management concepts and practices are comprehended, construed and employed through the region. The majority of developed supply chain management and risk management models are currently entrenched in the US and Europe. Consequently, this research is of high significance since its essential aim was to investigate these concepts and models, in particular, one focused on Africa. This approach enabled the thesis to examine and test components related to SCRM, such as risk categories, risk assessment and risk strategies, in the electrical energy sector in South Africa. The study in this manner offers knowledge that was not otherwise accessible in earlier research. In pursuit of meeting the requirements of the research questions, the supply chain department in the electrical energy supplier was researched. This study adopted the non-probability sampling approach utilising the purposive sampling technique to choose the sampling components from the target population. Data was collected by way of conducting semi-structured interviews and researcher observation, as well as additional documentation in various forms was collected. Interviews were transcribed and evaluated in conjunction with additional data collected during meetings and triangulated using researcher observation. Data interpretation and codification thereof was done using ATLAS.ti 8 by which, twenty-five themes emerged from this study. Supply chain risks comprise value streams; information and affiliations; supply chain activities; and external situations. Among these, information and relationships risks were found to produce selfupgrading risk loops, thereby generating consequent risk impacts after disturbances. To mitigate these risks, the case firm must engage in local and international supply chain implemented strategies, such as building a stable supply chain network, leveraging supply chain information, leveraging outsourcing contracts and developing supply-chain risk collaboration partnerships, although the level of implementation depends on the business context. Among the ten identified themes, building a stable supply chain and developing supply chain collaboration strategies can be useful in strengthening both robustness and resilience in supply chain risk management. Customer orientation had positive impacts on all themes, but disruption orientation and quality orientation influenced only certain types of strategies. The study makes ten recommendations, which can be implemented by the case firm; the results of the interviews are evidence that all the tools are available. The thesis concludes with a summary of overall findings and areas for further research are also highlighted.
D. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supply chains; Supply chain risk; Mitigation; Supply Chain Risk Management (SCRM); Business logistics.; Renewable energy resources -- South Africa.; Risk assessment.; Risk -- Measurement.; Dissertations, Academic -- South Africa.